Rescue of spinal muscular atrophy mouse models with AAV9-Exon-specific U1 snRNA. Issue 14 (25th May 2019) - Donadon, Irving; Bussani, Erica; Riccardi, Federico; Licastro, Danilo; Romano, Giulia; Pianigiani, Giulia; Pinotti, Mirko; Konstantinova, Pavlina; Evers, Melvin; Lin, Shuo; Rüegg, Markus A; Pagani, Franco
Abstract: Spinal Muscular Atrophy results from loss-of-function mutations in SMN1 but correcting aberrant splicing of SMN2 offers hope of a cure. However, current splice therapy requires repeated infusions and is expensive. We previously rescued SMA mice by promoting the inclusion of a defective exon in SMN2 with germline expression of Exon-Specific U1 snRNAs (ExspeU1). Here we tested viral delivery of SMN2 ExspeU1s encoded by adeno-associated virus AAV9. Strikingly the virus increased SMN2 exon 7 inclusion and SMN protein levels and rescued the phenotype of mild and severe SMA mice. In the severe mouse, the treatment improved the neuromuscular function and increased the life span from 10 to 219 days. ExspeU1 expression persisted for 1 month and was effective at around one five-hundredth of the concentration of the endogenous U1snRNA. RNA-seq analysis revealed our potential drug rescues aberrant SMA expression and splicing profiles, which are mostly related to DNA damage, cell-cycle control and acute phase response. Vastly overexpressing ExspeU1 more than 100-fold above the therapeutic level in human cells did not significantly alter global gene expression or splicing. These results indicate that AAV-mediated delivery of a modified U1snRNP particle may be a novel therapeutic option against SMA.